2010
DOI: 10.1016/j.ijsu.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic Scalpel® compared with bipolar electro-cautery hemorrhoidectomy: A randomized controlled trial

Abstract: This study demonstrates significantly reduced postoperative pain after Harmonic Scalpel Hemorrhoidectomy compared with bipolar electro-cautery Hemorrhoidectomy. Most likely, this result came from the avoidance of excessive lateral thermal injury caused by bipolar electrocautery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…However, in our study the return time to work could not be studied. Abo Hasem et al [20] noticed a P a g e / S a y f a | 13 significant difference in the time needed to return to work in favor to the HS method than the conventional one. Seventy-five percent of the patients in HS Group reported full-time return to work within the first two weeks postoperatively while for CH Group, this was true only for forty-five percent of the patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study the return time to work could not be studied. Abo Hasem et al [20] noticed a P a g e / S a y f a | 13 significant difference in the time needed to return to work in favor to the HS method than the conventional one. Seventy-five percent of the patients in HS Group reported full-time return to work within the first two weeks postoperatively while for CH Group, this was true only for forty-five percent of the patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…Harmonic scalpel achieved favorable postoperative pain scores compared with open or closed hemorrhoidectomy with scissors and/or monopolar or bipolar electrocautery in a number of prospective randomized studies [14][15][16][17][18][19]. The difference in pain was attributed to avoidance of lateral thermal energy in harmonic scalpel as opposed to electrocautery.…”
Section: Discussionmentioning
confidence: 99%
“…6 and Abo hashem et al, (2010). 7 The later authors reported that pain at first defecation and at rest first and second week after surgery was significantly lower in HS group then MM group. Armstrong et al, (2001) reported that postoperative pain was significantly less in the HS group.…”
Section: Graph 4: Postoperative Complications In Patients Treated Bymentioning
confidence: 92%